Push-pull current amplifiers for digital audio paths settings analyzer - Азаров, О. Д.; Крупельницький, Л. В.; Теплицький, М. Ю. (Problems of Informatization and Control, 2014)
The article discusses the possibility of improving the performance of the audio paths settings analyzer through the use of push-pull direct-current amplifiers with selective feedback. The structural and functional schemes of high-speed amplifiers with low harmonic distortion and high signal / noise ratio, which allows to extend the range of its own and the measured parameters of the analyzer, were proposed